The effect of Nigella Sativa extract on Alpha-ketoglutarate activity and histopathologic changes on Rat liver induced by Monosodium glutamate - Eshami, Ala Shukri; mitaroem, Karyono; Sujuti, Hidayat; Ashour, Abdussalam (Journal of Tropical Life Science, 2015)
Monosodium glutamate (MSG) is a commonly used food additive and found in most soups, fish and processed meat. The use of MSG in food is growing. Irrational fear had increased in the last few years due to the adverse reactions and toxicity of MSG, which effect on the liver. Nigella sativa is used as traditional medicine for the treatment of many diseases, it has been extensively investigated in recent years, traditional medicine for the treatment of many disease due to its notable pharmacological properties. NS can inhibit oxidative stress. The present study was undertaken to investigate different Doses of Nigella sativa on alpha KGDH activity and liver histology of MSG induced rat. The animals (n=30) Were grouped A as (control), B treated with MSG 1g/kg, C MSG treated with NS 0.01g/kg, D MSG treated with NS 0.02g/kg, E MSG treated with NS 0.04g/kg and F treated with NS 0.02g/kg then we investigated the effect alpha KGDH activity by ELISA method and liver histopathology by light microscope. alpha KGDH activity were significantly increased in treatment MSG compared with treatment negative control, MSG + NS 0.1g/kg, MSG + NS 0.02g/kg, MSG + NS 0.04g/kg, and NS 0.02g/kg. The histological changes in group B and C showed disturbed liver architecture, hemorrhage in the central veins, areas of necrosis, vacuolation and increased inflammatory cells infiltration while group D showed central vein is normal and vacuolation of cytoplasm, group E showed more normal liver architecture as shown less vacuolation in cytoplasm, central vein is normal, and group F showed no pathologic changes.These finding showed that administration of MSG increase alpha KGDH and induced damage in liver tissue. Nigella sativa extract can reduce alpha KGDH and prevent liver damage induced by MSG.Keywords : Monosodium glutamate, Alpha-ketoglutarate Dehydrogenases, Nigella sativa and liver damage.